A lucky thing - Schertle, Alice; Minor, Wendell (San Diego : Harcourt Brace, 1999)
A collection of fourteen poems about nature, including "Calling the Sun," "Showing the Wind," and "Invitation from a Mole."
Keywords: Children$1 (Bs poetry, American.s; Nature -- Juvenile poetry; Nature -- Poetry; American poetry